Relación de los tratados y convenciones Interamericanos = Status of Inter-American treaties and conventions = Relação dos tratados e convenções Interamericanos = État des traités et des conventions Interaméricains. - Pan American Union. General Secretariat. (Tufts University. Tisch Library., 2017)
Volume 2 of 10.; Tisch Outsourced Digitization 2017-10-02